2014
DOI: 10.1037/xap0000005
|View full text |Cite
|
Sign up to set email alerts
|

Attentional retraining can reduce chocolate consumption.

Abstract: There is emerging evidence that attentional biases are related to the consumption of substances such as alcohol and tobacco, and that attentional bias modification can reduce unwanted consumption of these substances. We present evidence for the first time that the same logical argument applies in the food and eating domain. We conducted two experiments which used a modified dot probe paradigm to train undergraduate women to direct their attention toward ('attend') or away from ('avoid') food cues (i.e., pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 48 publications
9
116
2
1
Order By: Relevance
“…Moreover, attentional retraining affected chocolate consumption and craving, and participants in the avoid group ate less chocolate in a so-called taste test than did those in the attend group. 62,65 Similar encouraging results were found in two other recent studies. 63,64 In the first, groups were trained either to attend to healthy food or to attend to unhealthy food, and 33 Avoid (-)/control Yes No Amir et al 6 Avoid (-)/control Yes Yes Hazen et al 26 Avoid (-)/control Yes Yes Heeren et al 27 Avoid (-)/control Yes Yes See et al 28 Avoid (-)/control Yes Yes Heeren et al 29 Avoid (-)/control Yes No MacLeod et al 7 Avoid (-)/attend (+) Yes Yes Browning et al 19 Avoid (-)/attend (+) Yes Yes MacLeod et al 34 Avoid (-)/attend (+) Yes Yes Van Bockstaele et al 35 Avoid (-)/attend (+) Yes No Van Bockstaele et al 36 Avoid (-)/attend (+) Yes No Eldar et al 37 Avoid (-)/attend (+) Partly No O'Toole et al 38 Avoid (-)/attend (+) Partly No Heeren et al 39 Attend (-)/control Yes Yes Krebs et al 40 Attend (-)/control Yes Yes Hayes et al 41 Attend (+)/control Yes Yes Li et al 42 Attend (+)/control Yes Yes Taylor et al 43 Attend (+)/control Yes Yes Wadlinger et al 44 Attend (+)/control Yes Yes Cowart et al 46 Avoid (-) Not applicable Not applicable Amir et al 45 Avoid (-) Yes Yes Brosan et al 47 Avoid (-) Yes Yes Heeren et al 48 Avoid (-)/attend (+)/control Yes Yes Klumpp et al 49 Avoid (-)/attend (+)/control No No Boettcher et al 50 Attend ( 51 Avoid (-)/attend (+) Yes Yes Schoenmakers et al 10 Avoid (-)/control Yes No Schoenmakers et al 53 Avoid (-)/control Yes Partly Kerst et al 54 Avoid (-)/control Yes Partly Lopes et al …”
Section: Eating Behaviorsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, attentional retraining affected chocolate consumption and craving, and participants in the avoid group ate less chocolate in a so-called taste test than did those in the attend group. 62,65 Similar encouraging results were found in two other recent studies. 63,64 In the first, groups were trained either to attend to healthy food or to attend to unhealthy food, and 33 Avoid (-)/control Yes No Amir et al 6 Avoid (-)/control Yes Yes Hazen et al 26 Avoid (-)/control Yes Yes Heeren et al 27 Avoid (-)/control Yes Yes See et al 28 Avoid (-)/control Yes Yes Heeren et al 29 Avoid (-)/control Yes No MacLeod et al 7 Avoid (-)/attend (+) Yes Yes Browning et al 19 Avoid (-)/attend (+) Yes Yes MacLeod et al 34 Avoid (-)/attend (+) Yes Yes Van Bockstaele et al 35 Avoid (-)/attend (+) Yes No Van Bockstaele et al 36 Avoid (-)/attend (+) Yes No Eldar et al 37 Avoid (-)/attend (+) Partly No O'Toole et al 38 Avoid (-)/attend (+) Partly No Heeren et al 39 Attend (-)/control Yes Yes Krebs et al 40 Attend (-)/control Yes Yes Hayes et al 41 Attend (+)/control Yes Yes Li et al 42 Attend (+)/control Yes Yes Taylor et al 43 Attend (+)/control Yes Yes Wadlinger et al 44 Attend (+)/control Yes Yes Cowart et al 46 Avoid (-) Not applicable Not applicable Amir et al 45 Avoid (-) Yes Yes Brosan et al 47 Avoid (-) Yes Yes Heeren et al 48 Avoid (-)/attend (+)/control Yes Yes Klumpp et al 49 Avoid (-)/attend (+)/control No No Boettcher et al 50 Attend ( 51 Avoid (-)/attend (+) Yes Yes Schoenmakers et al 10 Avoid (-)/control Yes No Schoenmakers et al 53 Avoid (-)/control Yes Partly Kerst et al 54 Avoid (-)/control Yes Partly Lopes et al …”
Section: Eating Behaviorsupporting
confidence: 87%
“…Six studies were identified, [62][63][64][65][66][67] and their tasks did not vary substantially, as they all a SOA of 500 ms and 12-20 pairs of food as a stimulus, although five used pictures and one used words. The three studies that compared attend and avoid groups 62,65,66 found AB changes and a significant impact of training. In the study with obese participants, AB for food increased in the attend group and decreased in the avoid group, and the effects generalized to an independent measure of attentional bias.…”
Section: Eating Behaviormentioning
confidence: 99%
“…Evidence for food-related attention biases 111 craving or hunger, only Kemps et al (70) observed a change in craving for chocolate in line with change in attention bias for chocolate. The other studies did not find an effect of attention bias (modification) on self-reported craving.…”
Section: Attention Bias For Food and Cravingmentioning
confidence: 98%
“…One such factor is the present 'obesogenic' environment that is characterised by a wealth of highly palatable, energy-dense foods (3) . These foods are heavily represented in the visual environment for example, through advertising and it has been suggested that frequent exposure to these forms of food-related cues may impact on eating behaviours and food choices (4)(5)(6) .…”
Section: Incentive Sensitisation: Weight Status: Eye Tracking: Visualmentioning
confidence: 99%
“…One such factor is the present 'obesogenic' environment that is characterised by a wealth of highly palatable, energy-dense foods (3) . These foods are heavily represented in the visual environment for example, through advertising and it has been suggested that frequent exposure to these forms of food-related cues may impact on eating behaviours and food choices (4)(5)(6) .According to the theory of incentive sensitisation, 'addictive substances' modify reward-related pathways in the brain leading to hypersensitisation of rewardrelated stimuli (7) . This results in increased salience to reward-related stimuli resulting in these stimuli becoming more 'attention grabbing'.…”
mentioning
confidence: 99%